AUTOMATION AND ATTRITION: A REAL CHALLENGE FOR INFORMATION TECHNOLOGY (IT) ORGANIZATION - Gayathri, K.; Thaiyalnayaki, M. (International Journal of Psychosocial Rehabilitation, 2020)
Information Technology(IT) companies use various software tools, processes and applications to achieve better results at optimum cost. The world has undergone tremendous technological changes in the recent years and It has become inevitable to automate processes across the organizations. Automation enhances revenue productivity and deliver efficiency, with less manual intervention. Though the emerging technologies improves the productivity and efficiency, still it has its own pros and cons on human force.Initially, IT companies were hiring the employees (Fresh Graduates) in lakhs, which has gradually reduced to thousands. Four out of six Indian IT companies have reported a decline in the head count. Impact of automation and increased digitalization has resulted in reduced resource requirements - Increase productivity by reducing man power. A recent report in Business line has stated ‘Automation reduces hiring in big five IT companies by 24%’ which drives to massive attrition. This paper aims to figure out the possible ways to retrain the employees in the automated platform and effective methods to manage attrition in the cognitive era.